PENGARUH GAME INTERAKTIF QUIZWHIZZER TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Maghfirah Sawawi; Mety Liesdiani (Jurnal Muara Pendidikan, 2025)
This study aims to investigate the impact of using the interactive quizwhizzer game on the interest and learning outcomes of grade X students in SMA Negeri 1 Tanjungbumi. The problem of low interest and academic achievement of students in learning mathematics encourages the need for more participatory and enjoyable learning innovations. A quantitative method with a quasi-experimental design was used in this study. The research subjects were selected from a group of 31 grade X-1 students as a trial group (experiment) who received game-based learning with quizwhizzer media, while 30 grade X-3 students were involved as a comparison group (control) who took similar learning without the media. The instruments used included test sheets to assess student learning outcomes and questionnaires that measured student interest in learning mathematics. Given that the data were not normally distributed, the Kolmogorov-Smirnov and Mann-Whitney U tests were used to analyze the data. The results of the study revealed that the use of the quizwhizzer game significantly increased students' interest in learning and academic achievement in mathematics, with a significance value of 0.000 <0.05. This finding confirms that the application of interactive digital media not only encourages enthusiasm for learning, but also creates a learning atmosphere that is more lively, meaningful, and in line with the needs of today's generation of learners.